TRANSACTION COSTS STRUCTURE OF THE INVESTMENT CONSTRUCTION CYCLE STAGES - Asaul, Anatoly; Ivanov, Sergey (Journal of European Economy, 2017)
In this article there have been examined the economic problems of the Russian investment construction sector. The economical growth directions of economic activity «Construction» have been determined. Comparative analysis of key economical institutional indicators has been performed. Research and practice problematic of the development of Russian ICC – high transaction costs of investment construction cycle – has been actualized.